Merajut Harmoni: Peran Seni dan Budaya dalam Membentuk Sikap Hidup Generasi Muda - Ginting, Junita Setiana; Sumarno, Edi; Sitopu, Sapna; Lubis, Aziz Rizky (Jurnal Kewarganegaraan, 2025)
This study aims to analyze the role of arts and cultural skills in strengthening attitudes, tolerance, and harmony among the younger generation in Paya Itik Village, Galang District, Deli Serdang Regency. The research method uses data collection techniques in the form of interviews, observations, and documentation and is carried out using a participatory approach, various arts training programs, vocals, and traditional dances to encourage positive interactions between groups. The results of the study indicate that involvement in arts and cultural activities can significantly increase awareness and the importance of tolerance and strengthen social ties between young people from different backgrounds so that they can create regeneration with harmonious attitudes and tolerance. This study not only provides space to express the cultural identity of each group but also becomes a medium for building understanding and mutual respect. In conclusion, the development of arts and cultural skills has proven effective as a means of building social cohesion and creating a more harmonious and inclusive society. As a recommendation, efforts are needed to preserve culture through local wisdom-based education, cultural festivals, and historical documentation.